Antitrust in a world without scarcity: homemade competition and the atomization of the markets - Domingos Taufick, Roberto (Revista do IBRAC, 2023)
In 2014 Stanford's Professor Mark Lemley wrote the avant-garde and provocative article IP in a World Without Scarcity. There he claimed that, as technology lowers the costs to produce and distribute new products, inventors need less IP protection in order to get stimulated to innovate. In this article we will explore the implications for antitrust of abundance caused by technology. We claim that the ongoing democratization of production and distribution has allowed that a number of people produce anything from almost anywhere in the world, which might, in the near future, lead to an atomization of the markets and lower prices to marginal costs.